Should skin picking disorder be considered a diagnostic category? A systematic review of the evidence. (September 2019) - Jenkins, Zoe; Zavier, Hyacinta; Phillipou, Andrea; Castle, David
Objectives: The aim of this study was to conduct a systematic review of the literature to collect, analyse and synthesise the evidence on skin picking disorder as defined by Arnold's criteria or the Diagnostic and Statistical Manual of Mental Disorders – fifth edition (DSM-5) and to examine whether skin picking disorder warrants inclusion in the DSM-5 as a distinct disorder. Method: The databases CINAHL, Medline, Embase and PsycINFO were searched for articles published between January 2008 and May 2018. Eligible articles were empirical studies that used Arnold's or DSM-5 criteria to diagnose skin picking disorder, published in English, with participants aged 18 years or older. The methodological quality of included studies was assessed according to the National Health and Medical Research Council's guidelines and suggested nosological classification of skin picking disorder were summarised. Eligible studies were assessed against the five criteria proposed by Blashfield and colleagues to determine the validity of the inclusion of skin picking disorder in the DSM-5. Results: A total of 20 studies were considered eligible out of 1554. Most of the papers were case-control studies with small clinical samples. Only one out of Blashfield's five criteria was met; there were commonly accepted diagnostic criteria and assessment scales present in the literature. However, at the time of review, the criterion of 50 published articles (25 of which are required to be empirical) was not met; there had been no publication specifically assessing the clinical utility or validity of skin picking disorder and no studies addressing the differentiation of skin picking disorder from other obsessive-compulsive and related disorders. Conclusion: Only a small proportion of published studies on skin picking disorder have employed validated criteria. The current literature fulfills only one of Blashfield's five criteria for the inclusion of skin picking disorder as a specific entity in psychiatric diagnostic manuals. Further empirical studies on skin picking disorder are needed in order to substantiate skin picking disorder as a disorder distinct from related disorders under the obsessive-compulsive and related disorders category.